Firm growth in multinational corporate groups - Harald Oberhofer; Michael Pfaffermayr (University of Salzburg, Department of Social Sciences and Economics, 2010)
This paper formulates an econometric firm growth model that explicitly accounts for interdependence of growth performance within multinational corporate networks. We apply a recently introduced IV-estimation procedure for peer group effects to directly test for externalities within multinational corporate networks. Using European firm level data, our results reveal positive externalities within vertically organized multinational networks, while they are negative for horizontally organized ones. In the former case, multinational corporate groups are more stable and adjust faster on average. In the latter case, externalities lead to more heterogeneity in the firm growth processes within the network and slower average size adjustment.
Keywords: C21; F23; L23; L25; 330; Firm growth; Size Adjustment; Multinational Corporate Groups; Peer Group Effect Estimation